IL-6 Levels Analysis Controlled in Type 2 Diabetes Mellitus Patients and Uncontrolled - Moonika Todingan; Rachmawati Muhiddin; Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Interleukin   6 (IL-6) is one of the pro-inflammatory cytokines responsible for inducing tissue-specific and/or systemic inflammation, which is a major contributor to the induction of inflammation of pancreatic islet cells.  Inflammation of pancreatic cells causes impaired insulin secretion and Type 2 Diabetes Mellitus (T2DM). This study aims to determine the levels of IL-6 in T2DM patients with different levels of severity. A cross-sectional study of 46 subjects was performed with 21 in the controlled T2DM group and 25 in the uncontrolled T2DM group. Interleukin-6 levels were measured using the ELISA method. The statistical tests used were the Mann-Whitney test and the Spearman test. The test results were significant if the p-value <0.05. The level of IL-6 in uncontrolled T2DM was higher (64.00±77.65 pg/mL) than in controlled T2DM (31.25±11.04 pg/mL).  Although the levels in both groups were different, the value was not statistically significant (p=0.120). There was no significant correlation found between HbA1c and IL-6 (p=0.125, r =0.230). Several experimental studies have shown that IL-6 inhibits glucose-stimulated insulin secretion from pancreatic islets in experimental animals. However, some of them revealed that acute exposure to IL-6 did not appear to affect pancreatic islet cell function, which is still controversial today. This study found a tendency of increased IL-6 in high-severity T2DM compared to low-severity T2DM although not statistically significant. Further studies with more clinically homogeneous samples are still needed.